Comparison of the in-vitro efficacy of different mouthwash solutions targeting SARS-CoV-2 based on the European Standard EN 14476. (May 2021) - Steinhauer, K.; Meister, T.L.; Todt, D.; Krawczyk, A.; Paßvogel, L.; Becker, B.; Paulmann, D.; Bischoff, B.; Pfaender, S.; Brill, F.H.H.; Steinmann, E.
Summary: The outbreak of the SARS-CoV-2 pandemic is triggering a global health emergency alert. Until vaccination becomes available, a bundle of effective preventive measures is desperately needed. Recent research is indicating the relevance of aerosols in the spread of SARS-CoV-2. Thus, in this study commercially available antiseptic mouthwashes based on the active ingredients chlorhexidine digluconate and octenidine dihydrochloride (OCT) were investigated regarding their efficacy against SARS-CoV-2 using the European Standard 14476. Based on the requirement of EN 14476 in which reduction of at least four decimal logarithms (≥4 log10 ) of viral titre is requested to state efficacy, the OCT-based formulation was found to be effective within a contact time of only 15 s against SARS-CoV-2. Based on this in-vitro data the OCT mouthwash thus constitutes an interesting candidate for future clinical studies to prove its effectiveness in a potential prevention of SARS-CoV-2 transmission by aerosols.